Meningkatkan Keterampilan Berkomunikasi Siswa Kelas Iv Sekolah Dasar Menggunakan Kombinasi Model PBL, TTW, DAN SCRAMBLE - Nahdia; Aslamiah (CV. ITTC INDONESIA, 2023)
Quality education is an aspect that plays quite an important role in the 21st century. The low quality and quality of education will have an impact on the progress of the nation and state. The challenges of education in the 21st century require students to have skills, one of which is communication. The problem that occurred in this research was the low communication skills of students. This is because learning is one-way, less interesting and enjoyable, and not meaningful. Efforts that can be made to overcome this problem are by using a combination of Problem Based Learning, Think Talk Write, and Scramble models. The aim of this research is to analyze the improvement of students' communication skills using a combination of Problem Based Learning, Think Talk Write, and Scramble models. This research used the Classroom Action Research (PTK) method which was carried out in 3 meetings. The data taken is qualitative data obtained through observing students' communication skills. The research results showed that students' communication skills at meeting 1 obtained a classical percentage of 42.86%, meeting 2 obtained a classical percentage of 76.19%, and meeting 3 obtained a classical percentage of 95.24%. Based on the results obtained from this research, it can be concluded that the combination of Problem Based Learning, Think Talk Write, and Scramble models can improve students' communication skills